Kasus Pemerkosaan Pada Hewan Ditinjau Dari Aspek Sosiologi Hukum - Firstnandiar Glica Aini Suniaprily; Hanuring Ayu Ardhani Putri (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Globalization is currently like a knife for society, the positive side gives unlimited access to seek information, the negative side makes people access content that should not be accessed at their age. This negative side also raises social problems, namely deviant sexual behavior, deviant behavior which the author will discuss is animal rape which is a form of deviant sexual behavior, which is a behavior that is inhuman and not commonly practiced in society. Although not all deviant sexual behavior originates from the process of globalization, at present this is the factor that makes this immoral behavior more prevalent in social life. Deviant sexual behavior is closely related to a person's psychological aspects, therefore the role of legal sociology is needed to deal with and overcome this rare and unusual behavior, in addition to the role of legal positivism. Because of the important role of society and interaction between communities to find a way out so that behavior like this does not occur again in the social life of society.